Khulafaurrasyidin: Theological and Socio-Political Discourse During the Era of Caliph Abu Bakar As-Shiddiq - Yasir Maulana Rambe; Monika Sari (UIN Sunan Gunung Djati Bandung, 2026)
Abu Bakr As-Siddiq was one of the Prophet Muhammad's main companions and the first leader of Islam during the Khulafaurrayidin period. Abu Bakr's leadership was marked by various political upheavals. This study will discuss the discourse between theology and politics that occurred during the leadership of Caliph Abu Bakr As-Siddiq . This research uses a historical method using secondary sources. Caliph Abu Bakr had a different political legitimacy than Prophet Muhammad. The Caliph served as an enforcer of the law that had been perfected during the Prophet Muhammad's time. This difference in legitimacy resulted in political upheavals that often intersected with the realm of Islamic theology. The political upheavals during Caliph Abu Bakr As-Siddiq's leadership consisted of three main things: the successor to leadership after the death of Prophet Muhammad SAW, the Phenomenon of False Prophets, and the Refusal to pay zakat. These three phenomena are forms of discourse between theology and politics. These three problems were handled very well. Caliph Abu Bakr did not tolerate any form of violation of theological aspects. Keywords: Islam; Prophet Muhammad; Theology; Political; Abu Bakr